Configuring the caller in ambiguous encounters: volunteer handling of calls to Samaritans emotional support services - Pollock, Kristian; Moore, John; Coveney, Catherine; Armstrong, Sarah (Equinox Publishing, 2012)
This paper discusses volunteer strategies for handling and assessing calls to Samaritans emotional support services for the suicidal and despairing. It presents findings from the qualitative components of a two year mixed methods study based on an online caller survey, branch observations and interviews with volunteers and callers throughout the UK. A thematic analysis of the qualitative data analysis was undertaken using the principle of constant comparison. Many calls fell beyond the primary remit of a crisis service, and called for rapid attribution and assessment. Uncertainty about identifying ‘good’ calls and recognizing those which were not caused difficulty, frustration and negative attribution towards some callers. This paper presents our analysis of volunteers’ accounts of how they configure the caller in intrinsically uncertain and ambiguous encounters, and how such strategies relate to the formal principles of unconditional support and non-judgemental active listening espoused by the organization.